Strategic management during a pandemic - Kumar, Vikas (writer on industrial management); Gupta, Gaurav 1986- (New York, NY Routledge, an imprint of the Taylor & Francis Group, 2022)
"The COVID-19 pandemic changed world dynamics, working scenarios, as well as professional and emotional dimensions. The virus has emerged as a significant threat for the continuity of business. Keeping the gravity of the problem in mind, companies must understand the need for change and must now update their strategy to account for pandemics. The next pandemic may be more severe than the current one, meaning that organizations need to devise mechanisms and business models to fight with these situations and maintain the business continuity. They should not only look forward to saving plants, machinery and infrastructure, but also concentrate on employee welfare, customer engagement and satisfaction during this crisis time. The book will not only present the evidence of various effective solutions to run a business in the time of a pandemic, but will also put forward the new models and practices of business being followed by people at the time of crisis. It aims to create a bridge between existing business models and proposed business solutions, focusing on existing theories and most importantly case studies from the recent happenings. This rich collection of chapters will provide insights regarding the business challenges, opportunities, and practices during the pandemic situations like COVID-19, making it particularly valuable to researchers, academics, and students in the fields of strategic management, leadership and disaster management."-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Strategic planning; Organizational change; Crisis management; COVID-19 (Disease) -- Economic aspects